Development of STEAM-Based Project-Based Learning (PjBL) Mathematics Learning Tools to Improve Students’ Critical Thinking - Lilik Dian; Timbul Yuwono; Tatik Retno Murniasih (JMPM: Jurnal Matematika dan Pendidikan Matematika, 2026)
This study aims to develop and evaluate the feasibility of STEAM-based mathematics learning tools integrated with Project-Based Learning (PjBL) to enhance students’ critical thinking skills in probability learning. This research employed a Research and Development (R&D) design using the 4-D model (Define, Design, Develop, Disseminate). The developed products consisted of lesson plans, student worksheets (LKPD), and critical thinking assessment instruments. The validity of the instruments was evaluated through expert judgment, while practicality and effectiveness were tested through classroom implementation using a pretest–posttest design.The results indicated that the learning tools achieved a high level of validity (mean score = 97%) and demonstrated good reliability (ICC = 0.778). The practicality results showed that all stages of PjBL implementation were conducted optimally. The effectiveness analysis revealed a moderate improvement in students’ critical thinking skills (N-Gain = 0.59). Furthermore, a paired sample t-test indicated a statistically significant difference between pretest and posttest scores (p < 0.05). These findings confirm that STEAM-based PjBL learning tools are effective in improving students’ critical thinking skills.